Microbially conjugated bile salts found in human bile activate the bile salt receptors TGR5 and FXR - Ay, Ümran; Leníček, Martin; Haider, Raphael S; Classen, Arno; van Eijk, Hans; Koelfat, Kiran V K; van der Kroft, Gregory; Neumann, Ulf P; Hoffmann, Carsten; Bolm, Carsten; Olde Damink, Steven W M; Schaap, Frank G (Hepatology communications, 2024)
BACKGROUND: Bile salts of hepatic and microbial origin mediate interorgan cross talk in the gut-liver axis. Here, we assessed whether the newly discovered class of microbial bile salt conjugates (MBSCs) activate the main host bile salt receptors (Takeda G protein-coupled receptor 5 [TGR5] and farnesoid X receptor [FXR]) and enter the human systemic and enterohepatic circulation. METHODS: N-amidates of (chenodeoxy) cholic acid and leucine, tyrosine, and phenylalanine were synthesized. Receptor activation was studied in cell-free and cell-based assays. MBSCs were quantified in mesenteric and portal blood and bile of patients undergoing pancreatic surgery. RESULTS: MBSCs were activating ligands of TGR5 as evidenced by recruitment of Gsα protein, activation of a cAMP-driven reporter, and diminution of lipopolysaccharide-induced cytokine release from macrophages. Intestine-enriched and liver-enriched FXR isoforms were both activated by MBSCs, provided that a bile salt importer was present. The affinity of MBSCs for TGR5 and FXR was not superior to host-derived bile salt conjugates. Individual MBSCs were generally not detected (ie, < 2.5 nmol/L) in human mesenteric or portal blood, but Leu-variant and Phe-variant were readily measurable in bile, where MBSCs comprised up to 213 ppm of biliary bile salts. CONCLUSIONS: MBSCs activate the cell surface receptor TGR5 and the transcription factor FXR and are substrates for intestinal (apical sodium-dependent bile acid transporter) and hepatic (Na+ taurocholate co-transporting protein) transporters. Their entry into the human circulation is, however, nonsubstantial. Given low systemic levels and a surplus of other equipotent bile salt species, the studied MBSCs are unlikely to have an impact on enterohepatic TGR5/FXR signaling in humans. The origin and function of biliary MBSCs remain to be determined.
Keywords: játra; Receptors, G-Protein-Coupled; Bile Acids and Salts; Receptors, Cytoplasmic and Nuclear; žluč; transkripční faktory; Humans; Liver; receptory spřažené s G-proteiny; lidé; Bile; žlučové kyseliny a soli; receptory cytoplazmatické a nukleární; Transcription Factors